The uniqueness of the pepaccur tradition in strengthening social ties in Lampung - Pratiwi, Nisa; Karsiwan, Karsiwan; Ingle, Poonam (AL MA'ARIEF : Jurnal Pendidikan Sosial dan Budaya, 2025)
As cultural homogenization grows and local identities begin to fade, preserving oral traditions plays a more vital role in keeping communities connected. This study aims to examine the uniqueness and relevance of the pepaccur tradition in strengthening social ties within the Lampung community. This research employs a qualitative methodology with an ethnographic approach. Data were gathered through participatory observation, in-depth interviews with traditional practitioners, and a review of relevant literature. The analysis was conducted using interactive analysis techniques to explore the symbolic meanings and social functions embedded in the tradition. The findings indicate that pepaccur serves not only as a medium of customary communication but also as a unifying instrument that bridges diverse social groups through shared values, mutual respect, and cooperation. These findings have implications for social science education by highlighting the pedagogical value of integrating local traditions to promote understanding of social cohesion, identity, and cultural sustainability. The novelty of this study lies in its focus on pepaccur as a culturally embedded practice that contributes to the theoretical and practical discourse on local wisdom as a foundation for social harmony in multicultural settings.